PATTERNS FOR SUSTAINABLE USE OF THREATENED MEDICINAL PLANTS WITH HIGH MARKET REQUIREMENTS - Redzic, S.; Trakic, S.; Basic, H. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Due to the over-exploitation from their natural habitats many medicinal and aromatic plants are extremely threatened in the Western Balkan, but also in South-Eastern Europe. Some of them are included in both, the regional and the European Red list. However, a strong need for some of them exists on the markets, while an adequate replacement for diverse pharmaceutics and dietetics contained within them has not been found yet [1]. Such is also the case with the widely known and in ethnobotany frequently applied species Gentiana lutea ssp. symphyandra Murbeck that grows only in the high mountains of the Western Balkan [2]. This plant has been used to treat stomach and heart diseases. Its root (Gentianae radix) is becoming an increasingly demanded drug on the modern pharmaceutical market [3]. Therefore, gentian root is being exploited without any surveillance or control which leads to the drastic decrease in number of its natural populations in most of the investigated mountains. In some mountains this species has almost completely disappeared. Despite numerous conventions (such as CITES, CBD, Bern Convention), over 65 t of dried gentian root has been illegally exported to the European market from Bosnia and Herzegovina (which is the centre of its distribution) in the last year, which is an ongoing trend. This root reaches the European market as Taraxaci radix. In order to achieve a sustainable protection for this economically and pharmacologically threatened medicinal plant, it is necessary to increase the level of responsibility of not only local exporters but also of foreign importers. Both parties have to be forced to respect international documents on traffic and trade with threatened wild species. In order to protect this and other species, artificial propagation under in situ conditions has been initiated, whereby geological foundation (dolomites) and ratio between calcium and magnesium in the ground are very important. Extraordinary results in this respect have been achieved. Propagation attempts under ex situ conditions have not given the expected results. Directed and planned propagation of Gentiana lutea in natural conditions could contribute to its efficient protection, but could also help meet the requirements of the market which has to be subdued to stricter controls. References: 1. Redzic S (2006) Proc 1st IFOAM Intern Conf Organic Wild Production, 117-141. 2. Redzic SS (2007) Coll. Antropol. 31: 869-890. 3. Redzic S (2007) Planta Medica 73:1013.